KHAZANAH ULAMA NUSANTARA : Tafsir MurÄh LabÄ«d Karya Nawawi Banten - Tsalis Muttaqin (UIN Raden Mas Said Surakarta, 2015)
In the history of Islamic development has well noted thatthere was an Indonesian Islamic scholar that very much respected bymost of the Islamic scholar in the Middle East. In fact, he has gottenhonorary title Sayyid Ulama HijÄz. One of his famous work is MurÄhLabÄ«d. A side of making us, especially as Indonesian Muslim society beproud to that great work, this book also very much compatible to theIndonesian society, in which the majority are following Imam SyÄfiâ€ŸÄ«for their fiqh mazhab. This book has well known by pesantrencommunity in Indonesia, as well as the other Syaikh Nawawi works